Health-related quality of life outcomes from the CANDOR study in patients with relapsed or refractory multiple myeloma. Issue 12 (15th October 2021) - Siegel, David; Weisel, Katja; Zahlten-Kumeli, Anita; Medhekar, Rohan; Ding, Bifeng; Leleu, Xavier
Abstract: CANDOR (NCT03158688) compared carfilzomib, dexamethasone, and daratumumab (KdD) to carfilzomib and dexamethasone (Kd) in patients with relapsed/refractory multiple myeloma (RRMM). A secondary objective of CANDOR was to evaluate health-related quality of life (HRQoL) scores using the Global Health Status (GHS)/Quality of Life (QoL) domain of the EORTC QLQ-C30. Scores were compared between KdD and Kd using a restricted maximum likelihood-based mixed effects model for repeated measures. GHS/QoL completion rates were >81% for both arms. Higher GHS/QoL scores were observed with KdD versus Kd from Cycle 7–26. The overall least squares mean estimate (95% CI) of the difference between treatment arms was 0.06 (–2.39 to 2.50; p  = 0.96). In an exploratory analysis, 55.5% in the KdD arm and 43.0% in the Kd arm improved ≥10 points in GHS/QoL score from baseline. HRQoL was maintained with KdD, consistent with superior clinical benefit observed with KdD versus Kd in patients with RRMM.